Prevalence of comorbidities between mood and anxiety disorders: associated factors in a population sample of young adults in southern Brazil - Mariane Ricardo Acosta Lopez Molina; Bárbara Spessato; Karen Jansen; Ricardo Pinheiro; Ricardo Silva; Luciano Dias de Mattos Souza (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2014)
This research aims to evaluate factors associated with the presence of comorbidities between mood and anxiety disorders in young adults aged 18 to 24 years, from Pelotas, Rio Grande do Sul State, Brazil. This was a cross-sectional, population-based study with a probabilistic sample by conglomerates. The Mini International Neuropsychiatric Interview (MINI) was used to assess mood and anxiety disorders. The prevalence of mental disorders in the sample (n = 1,561) was of 26.8% of which 9.7% had comorbidities between mood and anxiety disorders. The prevalence of comorbidities on mood and anxiety disorders is almost three times higher among women than men (p < 0.001). Lower education levels, socioeconomic status (p < 0.001) and a history of divorced parents (p < 0.050) was associated with comorbidities between mood and anxiety disorders. The main conclusion is that social factors are highly associated with comorbidities between mood and anxiety disorders. Prevention strategies on mental health should focus particularly on women in vulnerable social conditions.